PENGARUH METODE PEMBELAJARAN FONIK UNTUK MENINGKATKAN KEMAMPUAN MEMBACA PERMULAAN SISWA KELAS 1A DI UPT SDN 002 PENGHIDUPAN : PENGARUH METODE PEMBELAJARAN FONIK UNTUK MENINGKATKAN KEMAMPUAN MEMBACA PERMULAAN SISWA KELAS 1A DI UPT SDN 002 PENGHIDUPAN - Dini Suciani; Febrina Dafit (STKIP Subang, 2025)
This study aims to determine the effect of phonics learning methods to improve thebeginning reading skills of class 1A students at UPT SDN 002 Penghidupan. Thisstudy is a type of pre-experimental research with a one group pretest-posttestresearch design. The population in this study were all class 1 students at UPT SDN002 Penghidupan. The sample of this study was class 1A students totaling 28students at UPT SDN 002 Penghidupan. The research data were obtained from thebeginning reading ability test conducted with a pretest and posttest to determine theresults of its influence. The results of this study indicate that using the phonicslearning method has an effect on students' beginning reading skills. Based on theresults of the posttest average higher than the pretest average, namely the posttestaverage of 71.07 and the pretest average value of 40.04, in the sense that theapplication of the phonics learning method after the pretest can affect students'beginning reading skills, as seen from the average value of the pretest to theposttest average increasing very high. Based on the test and based on thehypothesis obtained using simple linear regression, a significance value of 0.000<0.05 was obtained, meaning that the phonics learning method has a significanteffect on the beginning reading ability of class 1A students at UPT SDN 002Penghidupan. So it can be concluded that the use of the phonics learning methodhas a significant effect on the beginning reading ability of class 1A students at UPTSDN 002 Penghidupan.